Bongoût no 1321 "lithographie d'art pute" : sub-graphik-zine - Bernhart, Antoine 1950-; Bolino, Pakito 1966-; Gfeller, Meeloo 1973-; Dion, MissCandy; 44; Léo 1971-; Yvang 1971- (Bongoût, 1998)
Grand format plié en 3, patchwork d'illustrations en bichromie. (www.graphzines.net)
Serigraphie
Keywords: Graphzine